Application of magnetic solid acid in preparation of glucose by high-frequency electromagnetic heating hydrolysis of polysaccharide

CN118326091BActive Publication Date: 2026-10-09UNIV OF SCI & TECH OF CHINA
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410425752.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-10
Publication Date
2026-10-09
Estimated Expiration
2044-04-10

AI Technical Summary

Benefits of technology

[0035] This invention uses inexpensive raw materials to prepare magnetic solid acids, which have the advantages of high selectivity, high catalyst acidity, simple operation, and mild reaction conditions. Due to their magnetic properties, the reacted solid material can be easily separated from the catalyst using a magnet for secondary use, reducing energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118326091B_ABST
    Figure CN118326091B_ABST
Patent Text Reader

Abstract

The application discloses application of a magnetic solid acid in preparation of glucose through polysaccharide high-frequency electromagnetic heating hydrolysis, and is to hydrolyze polysaccharide to prepare glucose through high-frequency electromagnetic heating in the presence of a magnetic solid acid catalyst with a core-shell structure. The preparation method of the magnetic solid acid with the core-shell structure is simple, the obtained magnetic solid acid has high acidity density, and the magnetic solid acid has high selectivity and yield when applied to a polysaccharide hydrolysis reaction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the application of magnetic solid acids in the high-frequency electromagnetic hydrolysis of polysaccharides to prepare glucose. Background Technology

[0002] Cellulose, as the most abundant renewable resource on Earth, plays a vital role in the sustainable development of humankind through its efficient utilization for the production of fuels and chemicals. Research on cellulose-based biomass conversion and its applications is increasing, and the conversion of platform molecules has been relatively thoroughly studied. However, the most critical issue currently is the targeted conversion of primary biomass, particularly the efficient hydrolysis of cellulose.

[0003] Cellulose is composed of glucose units linked by β-1,4-glycosidic bonds. The key to the hydrolysis-saccharification process is the activation of oxygen atoms on the glycosidic bonds, which in turn breaks the CO-glycosidic bonds, ultimately yielding soluble monosaccharides such as glucose. For basic research, cellulose's large molecular weight, compact tertiary structure, and small effective surface area lead to significant mass transfer resistance, difficulty in unraveling its complex structure, and numerous side reactions during conversion, all of which are key research areas and challenges. For practical applications, the directed hydrolysis of cellulose to produce glucose not only relates to the energy utilization of waste lignocellulose resources but also involves food safety issues. Therefore, developing an efficient hydrolysis system to reduce cellulose conversion costs and increase glucose yield is a crucial current challenge. Summary of the Invention

[0004] This invention addresses the shortcomings of existing technologies by providing an application of a magnetic solid acid in the high-frequency electromagnetic heating hydrolysis of polysaccharides to prepare glucose. The method for preparing the core-shell structured magnetic solid acid is simple, and the obtained magnetic solid acid has a high acidity density. In the presence of this magnetic solid acid, high-frequency electromagnetic heating is applied to the polysaccharide hydrolysis reaction, and the combined effect of both improves the selectivity and yield of the hydrolysis.

[0005] This invention relates to the application of magnetic solid acid in the high-frequency electromagnetic heating hydrolysis of polysaccharides to prepare glucose.

[0006] Specifically, glucose is prepared by hydrolyzing polysaccharides using magnetic solid acid as a catalyst and high-frequency electromagnetic heating.

[0007] The magnetic field range during high-frequency electromagnetic heating is 10-500KHz, preferably 300-500KHz.

[0008] In the specific reaction, a 15mL pressure-resistant tube was used as the reaction vessel, into which 400mg of reaction substrate, 400mg of magnetic solid acid catalyst, 10mL of water, and a high-temperature resistant magnetic ball were added. The equipment parameters were set as follows: power 4.2KW, frequency 380KHz, and relay setting: 40s operation followed by 4s stop cycle.

[0009] The reaction substrate polysaccharide refers to a sugar whose structural unit is glucose and is formed by glycosidic bonds, including one or more of cellobiose, starch, cellulose, cotton, and paper.

[0010] Pretreatment of polysaccharides before hydrolysis yields better results. This pretreatment includes mechanical ball milling and / or ionic liquid treatment.

[0011] Examples of preprocessing methods are as follows:

[0012] Weigh 40g of [BMIM]Cl ionic liquid into a 250mL round-bottom flask, add a small amount of water to dissolve the ionic liquid, and after the solution becomes clear and transparent, perform vacuum rotary evaporation. Once the solution becomes gel-like, add 2g of cellulose and heat and stir at 60-120℃ for 4-8 hours. You will see the cellulose dissolve into the [BMIM]Cl, and the solution will become clear and transparent. Then stop heating and quickly add purified water while stirring. Continue stirring until there are no large solid lumps in the solution, and then perform rotary centrifugation at 10000rpm / min for 10min. The evaporated liquid is recycled as [BMIM]Cl ionic liquid through vacuum rotary evaporation. The remaining solid is dried in a vacuum oven at 80℃.

[0013] The magnetic solid acid has a core-shell structure, with a magnetic material as the core and an outer shell material whose surface is modified with acidic groups and adsorption groups.

[0014] The magnetic solid acid is prepared by the following method:

[0015] By encapsulating different magnetic cores within shells of different properties, a magnetic solid acid precursor with a core-shell structure is obtained. Then, by sequentially modifying the surface with adsorption groups and sulfonic acid groups, a magnetic solid acid can be obtained.

[0016] The magnetic core is a magnetic material, including one or more of Fe3O4, Fe, Co, and Ni.

[0017] The outer shell includes one or more of the following: carbon shell, SiO2 shell, and nitrogen-containing carbon shell.

[0018] The adsorption group refers to a weakly acidic group that binds to a glycosidic bond, including one or more of -Cl, -OH, and -COOH.

[0019] The preparation method of the magnetic solid acid is illustrated below with an example:

[0020] Step 1: Preparation of porous Fe2O3 nanorod precursor

[0021] 60-150 mmol of ferric chloride hexahydrate (FeCl3·6H2O) was dissolved in 320 mL of deionized water. After dissolution by magnetic stirring, 80 mL of sodium hydroxide solution with a concentration of 4-8 mol / L was slowly added dropwise. The mixture was stirred vigorously at room temperature for 3 h, then heated to 80 °C and reacted at the original stirring rate for 4 h. After the reaction solution cooled to room temperature, the resulting mixture was centrifuged (10000 rpm / min, 10 min) to obtain a yellowish-brown precipitate. The precipitate was washed three times with deionized water and anhydrous ethanol, respectively. After centrifugation, it was dried in a vacuum drying oven at 80 °C for 12 h to obtain the dried FeOOH material. Then, it was calcined in a muffle furnace under the conditions of heating to 200-300 °C at a rate of 5 °C / min and holding for 120 min to obtain brownish-red Fe2O3 nanorods.

[0022] Step 2: Preparation of carbon-encapsulated magnetic Fe3O4 nanorods

[0023] Weigh out 20-60g of glucose monohydrate (C6H) 12 Anhydrous ethanol (OH) was dissolved in 400 ml of an ethanol-water solution (volume ratio: anhydrous ethanol: water = 2:1). Then, 8 g of Fe2O3 nanorods prepared in step 1 were added, ultrasonically dispersed, and then transferred to a hydrothermal reactor. The mixture was then hydrothermally reacted at 190 °C for 12 h in a homogeneous reactor to obtain a carbon precursor. The solid was then evaporated using a rotary evaporator and vacuum dried at 80 °C for 12 h in a vacuum drying oven. The dried solid was then calcined in a tube furnace under the conditions of heating to 500-900 °C at a rate of 5 °C / min and holding for 2 h. After cooling to room temperature, the solid was removed.

[0024] In this step, Fe2O3 is reduced to Fe3O4 by the carbon that encapsulates it. The material obtained in step 2 is abbreviated as Fe3O4@C.

[0025] Step 3: Nitric acid pretreatment

[0026] The carbon-coated magnetic Fe3O4 nanorods prepared in step 2 were crushed and ground and passed through a 60-200 mesh sieve. They were then added to a 100 mL solution of 10% nitric acid. The mixture was transferred to a 350 mL pressure-resistant tube, protected with argon gas, and the tube was tightened. The mixture was then reacted in an oil bath at 80 °C for 1-4 h. The tube was then washed with deionized water and centrifuged until the washing solution was neutral.

[0027] The 10% nitric acid used in this step is prepared from a 67% nitric acid standard solution.

[0028] The material obtained in step 3 is abbreviated as Fe3O4@C1. Compared with Fe3O4@C, Fe3O4@C1 has a larger specific surface area in its carbon layer, and its surface is activated by nitric acid and modified with some weakly acidic adsorption groups of -OH and -COOH.

[0029] Step 4: Sulfonation of Fe3O4@C1 nanorods

[0030] Add 8g of Fe3O4@C1 nanorods prepared in step 3 to 80mL of concentrated sulfuric acid and mix them in a 350mL pressure-resistant tube under argon protection. Then tighten the cap and stir the reaction at 150-300℃ for 12-48h. After the reaction is complete, wash with deionized water and centrifuge until the washing liquid is neutral to obtain the magnetic solid acid Fe3O4@C1-SO3H with a core-shell structure.

[0031] The concentrated sulfuric acid used in this step is a 98% concentrated sulfuric acid standard solution.

[0032] Acidity determination (acid-base titration): 0.1 g of magnetic solid acid catalyst was added to 20 mL of 1-3 mol / L NaCl solution and stirred at room temperature for 24 h. The solution was then titrated with NaOH (250 mL water + 50 mg NaOH). Because solid sodium hydroxide is highly susceptible to moisture in air, simply weighing the solution to prepare it is insufficient to determine the true concentration of sodium hydroxide. Therefore, potassium hydrogen phthalate was used to titrate the sodium hydroxide concentration.

[0033] Determination of sodium hydroxide concentration: Weigh 50 mg of potassium hydrogen phthalate solid and dissolve it in 100 mL of water (concentration 2.45 mmol / L). Then, titrate the known concentration of potassium hydrogen phthalate with the prepared sodium hydroxide solution. Titrate three times and take the average value. Each titration uses 20 mL of potassium hydrogen phthalate. The required volumes of sodium hydroxide solution for the three titrations are V1, V2, and V3, respectively. The final concentration of the sodium hydroxide solution is: 2.45 * 0.020 / (V1 + V2 + V3) / 3 = M NaOH mmol / L. The final titration yields V mL of NaOH solution, therefore the catalyst acidity is: M NaOH *V*10=M 酸 mmol / g.

[0034] The beneficial effects of this invention are reflected in:

[0035] This invention uses inexpensive raw materials to prepare magnetic solid acids, which have the advantages of high selectivity, high catalyst acidity, simple operation, and mild reaction conditions. Due to their magnetic properties, the reacted solid material can be easily separated from the catalyst using a magnet for secondary use, reducing energy consumption.

[0036] Electromagnetically inductive magnetic solid acid provides a unique solution for the efficient and targeted hydrolysis of cellulose to produce glucose. In traditional thermochemical reactions, solid acid transfers heat through the reaction solvent, resulting in high temperatures and harsh conditions throughout the reaction system. In contrast, electromagnetic induction heating generates heat in situ in the magnetic conductor material through eddy currents or hysteresis losses, offering not only high energy efficiency but also rapid heat transfer. This invention employs high-frequency electromagnetic induction heating, which, compared to traditional external heating, exhibits higher selectivity and yield in polysaccharide hydrolysis, demonstrating strong industrial application prospects and widespread value. Attached Figure Description

[0037] Figure 1 This is a schematic diagram of the preparation process of the present invention.

[0038] Figure 2 Photograph of the high-frequency electromagnetic induction device used in this invention.

[0039] Figure 3 The image shows the XRD pattern of Fe3O4@C1-SO3H prepared according to this invention.

[0040] Figure 4 This is a SEM image of Fe3O4@C1-SO3H prepared in this invention. Detailed Implementation

[0041] The technical solution of the present invention will be further analyzed and explained through specific embodiments below.

[0042] Setup and parameter settings for electromagnetic induction equipment:

[0043] The high-frequency electromagnetic induction device used in this invention has a maximum power of 10KW and features both water-cooling and air-cooling systems. The device's operating status is controlled by relays. Other supporting equipment includes a magnetic stirrer, an infrared imager, a magnetic field frequency detector, and a magnetic field detector. The device uses a custom-made coil with two turns and four loops, and an inner diameter of 26mm.

[0044] During the reaction, a 15 mL pressure-resistant tube was used as the reaction vessel, into which 400 mg of reactant, 400 mg of catalyst, 10 mL of water, and a high-temperature resistant magnetic ball were added.

[0045] In practice, the deionized water used is 1.5L of Wahaha purified water.

[0046] In practice, the hydrothermal reactor used in the hydrothermal process is a 500mL titanium hydrothermal reactor, and the rotation speed of the homogeneous reactor is set to 60 rpm.

[0047] In practice, the conditions used in the rotary evaporation process are a vacuum of 25 mbar, a rotation speed of 80 rpm, and a temperature of 60°C.

[0048] In practice, a 10KW ultra-high frequency electromagnetic induction device is used for heating, equipped with a magnetic stirrer and a frequency detector to measure the real-time frequency. The operation of the electromagnetic heating device is controlled by a relay. Before starting the equipment, the water-cooling and air-cooling systems must be turned on to ensure safety. When placing the reaction tube in the coil, ensure that the magnetic particle at the bottom of the reaction tube is not within the magnetic field generated by the coil to prevent it from being heated. During operation, ensure that the water temperature flowing out of the water-cooling system does not become too high to protect the equipment. The shutdown procedure is as follows: after turning off all electrical equipment, finally turn off the water-cooling and air-cooling systems to protect the equipment.

[0049] Example 1: Preparation of magnetic solid acids with core-shell structure

[0050] 1. Preparation of porous Fe2O3 nanorod precursors

[0051] 120 mmol (32.4 g) of ferric chloride hexahydrate (FeCl3·6H2O) was dissolved in 320 mL of deionized water. After dissolving with magnetic stirring, 80 mL of 6.25 mol / L sodium hydroxide solution (20 g NaOH + 80 mL water) was slowly added dropwise. The mixture was stirred vigorously at room temperature for 3 h, then heated to 80 °C and reacted at the original stirring rate for 4 h. After the reaction solution cooled to room temperature, the resulting mixture was centrifuged (10000 rpm / min, 10 min) to obtain a yellowish-brown precipitate. The precipitate was washed three times with deionized water and anhydrous ethanol, respectively. After centrifugation, it was dried in a vacuum drying oven at 80 °C for 12 h to obtain the dried FeOOH material. Then, it was calcined in a muffle furnace under the conditions of heating to 250 °C at a rate of 5 °C / min and holding for 120 min to obtain brownish-red Fe2O3 nanorods.

[0052] 2. Preparation of carbon-coated magnetic Fe3O4 nanorods

[0053] Weigh out 40g of glucose monohydrate (C6H) 12 The Fe2O3 nanorods prepared in step 1 were dissolved in 400 ml of anhydrous ethanol-water solution (volume ratio: anhydrous ethanol: water = 2:1). Then, 8 g of Fe2O3 nanorods prepared in step 1 were added, ultrasonically dispersed, and then transferred to a hydrothermal reactor. The mixture was then hydrothermally reacted at 190 °C for 12 h in a homogeneous reactor to obtain a carbon precursor. The solid was then evaporated using a rotary evaporator and vacuum dried at 80 °C for 12 h in a vacuum drying oven. The dried solid was then calcined in a tube furnace under the conditions of heating to 600 °C at a rate of 5 °C / min and holding for 2 h. After cooling to room temperature, the solid was removed.

[0054] In this step, Fe2O3 is reduced to F3O4 by the carbon that encapsulates it. The material obtained in step 2 is abbreviated as Fe3O4@C.

[0055] 3. Introduction of adsorption groups

[0056] The carbon-coated magnetic Fe3O4 nanorods prepared in step 2 were crushed and ground and passed through a 120-mesh sieve. They were then added to a 100 mL solution of 10% nitric acid. The mixture was transferred to a 350 mL pressure-resistant tube, protected with argon gas, and the tube was tightened. The mixture was then reacted in an oil bath at 80 °C for 2 h. After washing with deionized water, the mixture was centrifuged until the washing solution was neutral.

[0057] The 10% nitric acid used in this step is prepared from a 67% nitric acid standard solution.

[0058] The material obtained in step 3 is abbreviated as Fe3O4@C1. Compared with Fe3O4@C, Fe3O4@C1 has a larger specific surface area in its carbon layer, and its surface is activated by nitric acid and modified with some weakly acidic adsorption groups of -OH and -COOH.

[0059] 4. Sulfonation of Fe3O4@C1 nanorods

[0060] 8g of Fe3O4@C1 nanorods prepared in step 3 were added to 80mL of concentrated sulfuric acid and mixed in a 350mL pressure-resistant tube under argon protection. The cap was then tightened and the mixture was stirred at 250℃ for 24h. After the reaction was completed, the mixture was washed with deionized water and centrifuged until the washing liquid was neutral to obtain Fe3O4@C1-SO3H, a magnetic solid acid with a core-shell structure.

[0061] The concentrated sulfuric acid used in this step is a 98% concentrated sulfuric acid standard solution.

[0062] Acidity determination (acid-base titration): 0.1 g of magnetic solid acid catalyst was added to 20 mL of 2 mol / L NaCl solution and stirred at room temperature for 24 h. The solution was then titrated with NaOH (250 mL water + 50 mg NaOH). Because solid sodium hydroxide is highly susceptible to moisture in air, simply weighing and preparing the solution cannot determine the true concentration of sodium hydroxide. Therefore, potassium hydrogen phthalate was used to titrate the sodium hydroxide concentration.

[0063] Sodium hydroxide concentration determination: Weigh 50 mg of potassium hydrogen phthalate solid and dissolve it in 100 mL of water (concentration 2.45 mmol / L). Then, titrate the known concentration of potassium hydrogen phthalate with the prepared sodium hydroxide solution. Titrate three times and take the average value. Each titration uses 20 mL of potassium hydrogen phthalate. The required volumes of sodium hydroxide solution for the three titrations are 9.3 mL, 9.3 mL, and 9.4 mL, respectively. Take the average value of 9.33 mL. The final concentration of the sodium hydroxide solution is: 2.45 * 0.020 / 0.00933 = 5.25 mmol / L. Finally, 36.2 mL of NaOH solution is titrated. Therefore, the catalyst acidity is: 5.25 * 0.0362 * 10 = 1.90 mmol / g.

[0064] Example 2: Preparation of glucose from polysaccharide by directed hydrolysis

[0065] Weigh 400mg Fe3O4@C1-SO3H and 400mg cellobiose and add them to a 15mL pressure-resistant tube. Then add 10mL of deionized water and a high-temperature resistant magnetic dome. Finally, tighten the cap and fix it inside the coil of the high-frequency electromagnetic induction device, ensuring that the magnetic dome at the bottom is below the coil (to keep the magnetic dome away from the magnetic field and prevent it from being heated).

[0066] Reaction conditions: rotation speed 1000 rpm, reaction time 3 h, magnetic field strength 0.5 T, magnetic field frequency 380 kHz, relay operation set to cycle for 40 s on and 4 s off. After the reaction, the product was detected using HPLC (High Performance Liquid Chromatography), and the yield was calculated using the standard curve method (using glucose as a standard solution).

[0067] The detection conditions were as follows: column: SUGAR-SH1011, column temperature: 30℃, detector: differential refractive index detector (2414RI Detector), mobile phase: 5 mmol / L sulfuric acid, flow rate: 0.6 mL / min.

[0068] In comparison, the operation process was similar to that of Example 2 above, except that the electromagnetic heating method was replaced with traditional oil bath heating at 150°C for 3 hours. The reaction results are shown in Table 1 below:

[0069] Table 1

[0070]

[0071] The results showed that, compared with traditional heating methods, electromagnetic heating achieved a 100% conversion rate of cellobiose under the same conditions.

[0072] Example 3: Preparation of glucose from polysaccharide by directed hydrolysis

[0073] Weigh 400mg Fe3O4@C1-SO3H and 400mg soluble starch and add them to a 15mL pressure-resistant tube. Then add 10mL deionized water and a high-temperature resistant magnetic dome. Finally, tighten the cap and fix it inside the coil of the high-frequency electromagnetic induction device, ensuring that the magnetic dome at the bottom is below the coil (to keep the magnetic dome away from the magnetic field and prevent it from being heated).

[0074] Reaction conditions: rotation speed 1000 rpm, reaction time 3 h, magnetic field strength 0.5 T, magnetic field frequency 380 kHz, relay operation set to cycle for 40 s on and 4 s off. After the reaction, the total reducing sugar yield of the reaction solution was determined by the 3,5-dinitrosalicylic acid method, and a standard curve of total reducing sugar was constructed (using cellobiose as the standard solution). The products were detected by HPLC (high performance liquid chromatography), and the yield was calculated using the standard curve method (using glucose as the standard solution).

[0075] The detection conditions were as follows: Total reducing sugar determination equipment: UV-Vis spectrophotometer; cuvettes: quartz cuvettes; detection wavelength: 540 nm; chromatographic column: SUGAR-SH1011; column temperature: 30℃; detector: differential refractive index detector (2414 RI Detector); mobile phase: 5 mmol / L sulfuric acid; flow rate: 0.6 ml / min.

[0076] In comparison, the operation process was similar to that of Example 3 above, except that the electromagnetic heating method was replaced with traditional oil bath heating at 150°C for 3 hours. Furthermore, again for comparison, the operation process was similar to that of Example 3 above, except that the reactant was changed to cellulose. The reaction results are shown in Table 2 below. The results show that for the reaction of soluble starch and cellulose, the electromagnetic heating method generally yields better results than the traditional heating method.

[0077] Table 2

[0078]

[0079] Example 4: Preparation of glucose from polysaccharide by directed hydrolysis

[0080] Weigh 40g of [BMIM]Cl ionic liquid into a 250mL round-bottom flask, add a little water to dissolve the ionic liquid, and after the solution becomes clear and transparent, perform vacuum rotary evaporation. Once the solution becomes gel-like, add 2g of cellulose and heat and stir at 80℃ for 6 hours. You will see the cellulose dissolve into the [BMIM]Cl, and the solution will become clear and transparent. Then stop heating and quickly add purified water while stirring. Continue stirring until there are no large solid lumps in the solution, then centrifuge at 10000rpm / min for 10min. The evaporated liquid is recycled as [BMIM]Cl ionic liquid, and the remaining solid is dried in a vacuum oven at 80℃.

[0081] Weigh 400mg Fe3O4@C1-SO3H and 400mg of the above-treated cellulose and add them to a 15mL pressure-resistant tube. Then add 10mL of deionized water and a high-temperature resistant magnetic dome. Finally, tighten the cap and fix it inside the coil of the high-frequency electromagnetic induction device, ensuring that the magnetic dome at the bottom is below the coil (to keep the magnetic dome away from the magnetic field and prevent it from being heated).

[0082] Reaction conditions: rotation speed 1000 rpm, reaction time 3 h, magnetic field strength 0.5 T, magnetic field frequency 380 kHz, relay operation set to cycle for 40 s on and 4 s off. After the reaction, the total reducing sugar yield of the reaction solution was determined by the 3,5-dinitrosalicylic acid method, and a standard curve of total reducing sugar was constructed (using cellobiose as the standard solution). The products were detected by HPLC (high performance liquid chromatography), and the yield was calculated using the standard curve method (using glucose as the standard solution).

[0083] The detection conditions were as follows: Total reducing sugar determination equipment: UV-Vis spectrophotometer; cuvettes: quartz cuvettes; detection wavelength: 540 nm; chromatographic column: SUGAR-SH1011; column temperature: 30℃; detector: differential refractive index detector (2414 RI Detector); mobile phase: 5 mmol / L sulfuric acid; flow rate: 0.6 ml / min.

[0084] In comparison, the operation process was similar to that of Example 4, except that the reaction time was changed. The reaction results are shown in Table 3 below. This example demonstrates that after treating cellulose in the same way, the maximum total reducing sugar yield reached approximately 65% ​​with electromagnetic heating, while the maximum total reducing sugar yield with conventional heating was only about 50%. This proves the advantage of electromagnetic heating; its in-situ heating method improves the selectivity of the reaction, further avoids side reactions, and thus increases the yield.

[0085] Table 3

[0086]

[0087] Example 5: Preparation of glucose from polysaccharide by directed hydrolysis

[0088] Weigh 10g of cotton, pulverize it thoroughly with scissors, then wash it several times with deionized water and dry it thoroughly in an 80℃ vacuum oven.

[0089] Weigh 200g of [BMIM]Cl ionic liquid into a 500mL round-bottom flask, add a little water to dissolve the ionic liquid, and after the solution becomes clear and transparent, perform vacuum rotary evaporation. Evaporate until it becomes a gel, then add 10g of cotton wool. Heat and stir at 80℃ for 6 hours. The cotton wool will dissolve into the [BMIM]Cl, and the solution will become clear and transparent. Stop heating and quickly add purified water while stirring. Continue stirring until there are no large solid clumps. Then, centrifuge at 10000rpm / min for 10 minutes. The evaporated liquid is recycled as [BMIM]Cl ionic liquid. The remaining solid is dried in a vacuum oven at 80℃.

[0090] Weigh 400mg Fe3O4@C1-SO3H and 400mg of the above-treated cotton and add them to a 15mL pressure-resistant tube. Then add 10mL of deionized water and a high-temperature resistant magnetic dome. Finally, tighten the cap and fix it inside the coil of the high-frequency electromagnetic induction device, ensuring that the magnetic dome at the bottom is below the coil (to keep the magnetic dome away from the magnetic field and prevent it from being heated).

[0091] Reaction conditions: rotation speed 1000 rpm, reaction time 15 h, magnetic field strength 0.5 T, magnetic field frequency 380 kHz, relay operation set to cycle for 40 s on and 4 s off. After the reaction, the total reducing sugar yield of the reaction solution was determined by the 3,5-dinitrosalicylic acid method, and a standard curve of total reducing sugar was constructed (using cellobiose as the standard solution). The products were detected by HPLC (high performance liquid chromatography), and the yield was calculated using the standard curve method (using glucose as the standard solution).

[0092] The detection conditions were as follows: Total reducing sugar determination equipment: UV-Vis spectrophotometer; cuvettes: quartz cuvettes; detection wavelength: 540 nm; chromatographic column: SUGAR-SH1011; column temperature: 30℃; detector: differential refractive index detector (2414 RI Detector); mobile phase: 5 mmol / L sulfuric acid; flow rate: 0.6 mL / min.

[0093] In comparison, the operation process was similar to that of Example 5 above, except that the electromagnetic heating method was replaced with traditional oil bath heating at 150°C for 3 hours. Furthermore, also for comparison, the pretreatment process and reaction were similar to those of Example 5 above, except that the reactants were replaced with paper. The reaction results are shown in Table 4 below:

[0094] Table 4

[0095]

[0096] Example 6: Preparation of magnetic solid acids with core-shell structures

[0097] 1. Preparation of porous Fe2O3 nanorod precursors

[0098] 60 mmol (16.2 g) of ferric chloride hexahydrate (FeCl3·6H2O) was dissolved in 320 mL of deionized water. After dissolving with magnetic stirring, 80 mL of 6.25 mol / L sodium hydroxide solution (20 g NaOH + 80 mL water) was slowly added dropwise. The mixture was stirred vigorously at room temperature for 3 h, then heated to 80 °C and reacted at the original stirring rate for 4 h. After the reaction solution cooled to room temperature, the resulting mixture was centrifuged (10000 rpm / min, 10 min) to obtain a yellowish-brown precipitate. The precipitate was washed three times with deionized water and anhydrous ethanol, respectively. After centrifugation, it was dried in a vacuum drying oven at 80 °C for 12 h to obtain the dried FeOOH material. Then, it was calcined in a muffle furnace under the conditions of heating to 250 °C at a rate of 5 °C / min and holding for 120 min to obtain brownish-red Fe2O3 nanorods.

[0099] 2. Preparation of carbon-coated magnetic Fe3O4 nanorods

[0100] Weigh out 60g of glucose monohydrate (C6H) 12 The Fe2O3 nanorods prepared in step 1 were dissolved in 400 ml of anhydrous ethanol-water solution (volume ratio: anhydrous ethanol: water = 2:1). Then, 8 g of Fe2O3 nanorods prepared in step 1 were added, ultrasonically dispersed, and then transferred to a hydrothermal reactor. The mixture was hydrothermally reacted at 190 °C for 12 h in a homogeneous reactor to obtain a carbon precursor. The solid was then evaporated using a rotary evaporator and vacuum dried at 80 °C for 12 h in a vacuum drying oven. The dried solid was then calcined in a tube furnace under the conditions of heating to 800 °C at a rate of 5 °C / min and holding for 2 h. After cooling to room temperature, the solid was removed.

[0101] In this step, Fe2O3 is reduced to F3O4 by the carbon that encapsulates it. The material obtained in step 2 is abbreviated as Fe3O4@C.

[0102] 3. Introduction of adsorption groups

[0103] The carbon-coated magnetic Fe3O4 nanorods prepared in step 2 were crushed and ground and passed through a 100-mesh sieve. They were then added to a 100 mL solution of 10% nitric acid. The mixture was transferred to a 350 mL pressure-resistant tube, protected with argon gas, and the tube was tightened. The mixture was then reacted in an oil bath at 80 °C for 4 h. After washing with deionized water, the mixture was centrifuged until the washing solution was neutral.

[0104] The 10% nitric acid used in this step is prepared from a 67% nitric acid standard solution.

[0105] The material obtained in step 3 is abbreviated as Fe3O4@C1. Compared with Fe3O4@C, Fe3O4@C1 has a larger specific surface area in its carbon layer, and its surface is activated by nitric acid and modified with some weakly acidic adsorption groups of -OH and -COOH.

[0106] 4. Sulfonation of Fe3O4@C1 nanorods

[0107] 8g of Fe3O4@C1 nanorods prepared in step 3 were added to 80mL of concentrated sulfuric acid and mixed in a 350mL pressure-resistant tube under argon protection. The cap was then tightened and the mixture was stirred at 200℃ for 36h. After the reaction was completed, the mixture was washed with deionized water and centrifuged until the washing liquid was neutral to obtain the magnetic solid acid Fe3O4@C1-SO3H with a core-shell structure.

[0108] The concentrated sulfuric acid used in this step is a 98% concentrated sulfuric acid standard solution.

[0109] Acidity determination (acid-base titration): 0.1 g of magnetic solid acid catalyst was added to 20 mL of 2 mol / L NaCl solution and stirred at room temperature for 24 h. The solution was then titrated with NaOH (250 mL water + 50 mg NaOH). Because solid sodium hydroxide is highly susceptible to moisture in air, simply weighing and preparing the solution cannot determine the true concentration of sodium hydroxide. Therefore, potassium hydrogen phthalate was used to titrate the sodium hydroxide concentration.

[0110] Determination of sodium hydroxide concentration: Weigh 50 mg of potassium hydrogen phthalate solid and dissolve it in 100 mL of water (concentration 2.45 mmol / L). Then, titrate the known concentration of potassium hydrogen phthalate with the prepared sodium hydroxide solution. Perform three titrations and take the average value. Each titration uses 20 mL of potassium hydrogen phthalate. The required volumes of sodium hydroxide solution for the three titrations are 10 mL, 9.8 mL, and 9.9 mL, respectively. Take the average value of 9.9 mL. The final concentration of the sodium hydroxide solution is: 2.45 * 0.020 / 0.0099 =

[0111] 4.96 mmol / L. Finally, 24.6 mL of NaOH solution was titrated, therefore the catalyst acidity is: 4.96 * 0.0246 * 10 = 1.22 mmol / g.

[0112] Example 7: Preparation of glucose from polysaccharide by directed hydrolysis

[0113] Weigh 400mg Fe3O4@C1-SO3H and 400mg cellobiose and add them to a 15mL pressure-resistant tube. Then add 10mL of deionized water and a high-temperature resistant magnetic dome. Finally, tighten the cap and fix it inside the coil of the high-frequency electromagnetic induction device, ensuring that the magnetic dome at the bottom is below the coil (to keep the magnetic dome away from the magnetic field and prevent it from being heated).

[0114] Reaction conditions: rotation speed 1000 rpm, reaction time 3 h, magnetic field strength 0.5 T, magnetic field frequency 380 kHz, relay operation set to cycle for 40 s on and 4 s off. After the reaction, the product was detected using HPLC (High Performance Liquid Chromatography), and the yield was calculated using the standard curve method (using glucose as a standard solution).

[0115] The detection conditions were as follows: column: SUGAR-SH1011, column temperature: 30℃, detector: differential refractive index detector (2414RI Detector), mobile phase: 5 mmol / L sulfuric acid, flow rate: 0.6 mL / min.

[0116] In comparison, the operation process was similar to that of Example 7 above, except that the electromagnetic heating method was replaced with traditional oil bath heating at 150°C for 3 hours. The reaction results are shown in Table 5 below:

[0117] Table 5

[0118]

[0119] A comparison of the effect data in Table 5 and Table 1 shows that the magnetic solid acid with a core-shell structure prepared in Example 1 has a better promoting effect on the hydrolysis process of cellobiose.

[0120] Example 8: Preparation of glucose from polysaccharide by directed hydrolysis

[0121] Weigh 400mg Fe3O4@C1-SO3H and 400mg soluble starch and add them to a 15mL pressure-resistant tube. Then add 10mL deionized water and a high-temperature resistant magnetic dome. Finally, tighten the cap and fix it inside the coil of the high-frequency electromagnetic induction device, ensuring that the magnetic dome at the bottom is below the coil (to keep the magnetic dome away from the magnetic field and prevent it from being heated).

[0122] Reaction conditions: rotation speed 1000 rpm, reaction time 3 h, magnetic field strength 0.5 T, magnetic field frequency 380 kHz, relay operation set to cycle for 40 s on and 4 s off. After the reaction, the total reducing sugar yield of the reaction solution was determined by the 3,5-dinitrosalicylic acid method, and a standard curve of total reducing sugar was constructed (using cellobiose as the standard solution). The products were detected by HPLC (high performance liquid chromatography), and the yield was calculated using the standard curve method (using glucose as the standard solution).

[0123] The detection conditions were as follows: Total reducing sugar determination equipment: UV-Vis spectrophotometer; cuvettes: quartz cuvettes; detection wavelength: 540 nm; chromatographic column: SUGAR-SH1011; column temperature: 30℃; detector: differential refractive index detector (2414 RI Detector); mobile phase: 5 mmol / L sulfuric acid; flow rate: 0.6 ml / min.

[0124] In comparison, the operation process was similar to that of Example 8 above, except that the electromagnetic heating method was replaced with traditional oil bath heating at 150°C for 3 hours. Furthermore, also for comparison, the operation process was similar to that of Example 8 above, except that the reactant was changed to cellulose. The reaction results are shown in Table 6 below:

[0125] Table 6

[0126]

[0127] A comparison of the effect data in Table 6 and Table 2 shows that the magnetic solid acid with a core-shell structure prepared in Example 1 has a better promoting effect on the hydrolysis process of soluble starch and cellulose.

[0128] Example 9: Preparation of glucose from polysaccharide by directed hydrolysis

[0129] Weigh 40g of [BMIM]Cl ionic liquid into a 250mL round-bottom flask, add a little water to dissolve the ionic liquid, and after the solution becomes clear and transparent, perform vacuum rotary evaporation. Once the solution becomes gel-like, add 2g of cellulose and heat and stir at 80℃ for 6 hours. The cellulose will dissolve into the [BMIM]Cl, and the solution will become clear and transparent. Then stop heating and quickly add purified water while stirring. Continue stirring until there are no large solid lumps, then centrifuge at 10000rpm / min for 10min. The evaporated liquid is recycled as [BMIM]Cl ionic liquid, and the remaining solid is dried in a vacuum oven at 80℃.

[0130] Weigh 400mg Fe3O4@C1-SO3H and 400mg of the above-treated cellulose and add them to a 15mL pressure-resistant tube. Then add 10mL of deionized water and a high-temperature resistant magnetic dome. Finally, tighten the cap and fix it inside the coil of the high-frequency electromagnetic induction device, ensuring that the magnetic dome at the bottom is below the coil (to keep the magnetic dome away from the magnetic field and prevent it from being heated).

[0131] Reaction conditions: rotation speed 1000 rpm, reaction time 6 h, magnetic field strength 0.5 T, magnetic field frequency 380 kHz, relay operation set to cycle for 40 s on and 4 s off. After the reaction, the total reducing sugar yield of the reaction solution was determined by the 3,5-dinitrosalicylic acid method, and a standard curve of total reducing sugar was constructed (using cellobiose as the standard solution). The products were detected by HPLC (high performance liquid chromatography), and the yield was calculated using the standard curve method (using glucose as the standard solution).

[0132] The detection conditions were as follows: Total reducing sugar determination equipment: UV-Vis spectrophotometer; cuvettes: quartz cuvettes; detection wavelength: 540 nm; chromatographic column: SUGAR-SH1011; column temperature: 30℃; detector: differential refractive index detector (2414 RI Detector); mobile phase: 5 mmol / L sulfuric acid; flow rate: 0.6 ml / min.

[0133] In comparison, the operation process was similar to that of Example 9, except that the reaction time was changed. The reaction results are shown in Table 7 below:

[0134] Table 7

[0135]

[0136] A comparison of the effect data in Table 7 and Table 3 shows that, for the hydrolysis process of cellulose, the magnetic solid acid with a core-shell structure prepared in Example 1 has a better promoting effect, and has higher selectivity and yield at the same reaction time.

[0137] Example 10: Preparation of glucose from polysaccharide by directed hydrolysis

[0138] Weigh 10g of cotton, pulverize it thoroughly with scissors, then wash it several times with deionized water and dry it thoroughly in an 80℃ vacuum oven.

[0139] Weigh 200g of [BMIM]Cl ionic liquid into a 500mL round-bottom flask, add a little water to dissolve the ionic liquid, and after the solution becomes clear and transparent, perform vacuum rotary evaporation. Evaporate until it becomes a gel, then add 10g of cotton wool. Heat and stir at 80℃ for 6 hours. The cotton wool will dissolve into the [BMIM]Cl, and the solution will become clear and transparent. Stop heating and quickly add purified water while stirring. Continue stirring until there are no large solid clumps. Then, centrifuge at 10000rpm / min for 10 minutes. The evaporated liquid is recycled as [BMIM]Cl ionic liquid. The remaining solid is dried in a vacuum oven at 80℃.

[0140] Weigh 400mg Fe3O4@C1-SO3H and 400mg of the above-treated cotton and add them to a 15mL pressure-resistant tube. Then add 10mL of deionized water and a high-temperature resistant magnetic dome. Finally, tighten the cap and fix it inside the coil of the high-frequency electromagnetic induction device, ensuring that the magnetic dome at the bottom is below the coil (to keep the magnetic dome away from the magnetic field and prevent it from being heated).

[0141] Reaction conditions: rotation speed 1000 rpm, reaction time 15 h, magnetic field strength 0.5 T, magnetic field frequency 380 kHz, relay operation set to cycle for 40 s on and 4 s off. After the reaction, the total reducing sugar yield of the reaction solution was determined by the 3,5-dinitrosalicylic acid method, and a standard curve of total reducing sugar was constructed (using cellobiose as the standard solution). The products were detected by HPLC (high performance liquid chromatography), and the yield was calculated using the standard curve method (using glucose as the standard solution).

[0142] The detection conditions were as follows: Total reducing sugar determination equipment: UV-Vis spectrophotometer; cuvettes: quartz cuvettes; detection wavelength: 540 nm; chromatographic column: SUGAR-SH1011; column temperature: 30℃; detector: differential refractive index detector (2414 RI Detector); mobile phase: 5 mmol / L sulfuric acid; flow rate: 0.6 mL / min.

[0143] In comparison, the operation process was similar to that of Example 10 above, except that the electromagnetic heating method was replaced with traditional oil bath heating at a temperature of 150°C for 3 hours. Furthermore, also for comparison, the pretreatment process and reaction were similar to those of Example 10 above, except that the reactants were replaced with paper. The reaction results are shown in Table 8 below.

[0144] Table 8

[0145]

[0146] A comparison of the effect data in Table 8 and Table 4 shows that, for the hydrolysis process of cotton and paper, the magnetic solid acid with a core-shell structure prepared in Example 1 has a better promoting effect, and exhibits higher selectivity and yield at the same reaction time.

[0147] Example 11: Preparation of magnetic solid acids with core-shell structure

[0148] 1. Preparation of Fe3O4 nanoparticle precursor

[0149] 40 mmol (10.8 g) of ferric chloride hexahydrate (FeCl3·6H2O) and 20 mmol (5.5 g) of ferrous sulfate heptahydrate (FeSO4·7H2O) were dissolved in 250 mL of deionized water. The solution was magnetically stirred for 10 min at 85 °C under an argon atmosphere. Concentrated ammonia was then added dropwise to adjust the pH to 9-11, and the reaction was continued at 85 °C for 4 h. After the reaction was complete, the black precipitate was collected using a permanent magnet and washed with water until the washings were neutral. The precipitate was then washed three times with anhydrous ethanol and dried in a vacuum drying oven at 80 °C for 12 h to obtain dried Fe3O4 nanoparticles.

[0150] The concentrated ammonia solution used in this step is 25% concentrated ammonia solution by mass.

[0151] 2. Preparation of SiO2-coated magnetic Fe3O4 nanoparticles

[0152] 2 g of the Fe3O4 nanoparticles prepared in step 1 were added to 400 mL of anhydrous ethanol and pre-dispersed by sonication for 30 min at room temperature. The ethanol dispersion of Fe3O4 nanoparticles was stirred at room temperature, and 12 mL of concentrated ammonia and 4 mL of tetraethyl orthosilicate were slowly added. The reaction was then continued to be stirred at room temperature for 24 h. After the reaction was completed, the precipitate was collected using a permanent magnet and washed multiple times with ethanol. Then, it was dried in a vacuum drying oven at 80 °C for 12 h to obtain the SiO2-encapsulated magnetic Fe3O4 nanoparticles, denoted as Fe3O4@SiO2.

[0153] The concentrated ammonia solution used in this step is 25% concentrated ammonia solution by mass.

[0154] 3. Introduction of Cl-containing adsorption groups

[0155] Take 2g of Fe3O4@SiO2 obtained in step 2 and add it to 30mL of toluene. Then add 2g of 3-chloropropyltrimethoxysilane and heat under reflux at 120℃ with stirring for 12h. After the reaction is complete, cool to room temperature, collect the precipitate with a permanent magnet, wash it several times with ethanol, and then dry it in a vacuum drying oven at 80℃ for 12h to obtain a solid, denoted as Fe3O4@SiO2-Cl.

[0156] 4. Introduction of nitrogen-containing adsorption groups and sulfonic acid active sites

[0157] 1.5 g of Fe3O4@SiO2-Cl obtained in step 3 was added to 30 mL of N,N-dimethylformamide, followed by 1.2 g of p-aminobenzenesulfonic acid and 1.2 g of potassium carbonate. The mixture was heated to 100 °C and reacted for 24 h. After the reaction was completed, the mixture was cooled to room temperature, and the precipitate was collected using a permanent magnet. The precipitate was washed several times with water and ethanol, and then dried in a vacuum drying oven at 80 °C for 12 h to obtain a solid, denoted as Fe3O4@SiO2-SO3H.

[0158] Acidity determination (acid-base titration): 0.1 g of magnetic solid acid catalyst was added to 20 mL of 2 mol / L NaCl solution and stirred at room temperature for 24 h. The solution was then titrated with NaOH (250 mL water + 50 mg NaOH). Because solid sodium hydroxide is highly susceptible to moisture in air, simply weighing and preparing the solution cannot determine the true concentration of sodium hydroxide. Therefore, potassium hydrogen phthalate was used to titrate the sodium hydroxide concentration.

[0159] Sodium hydroxide concentration determination: Weigh 50 mg of potassium hydrogen phthalate solid and dissolve it in 100 mL of water (concentration 2.45 mmol / L). Then, titrate the known concentration of potassium hydrogen phthalate with the prepared sodium hydroxide solution. Titrate three times and take the average value. Each titration uses 20 mL of potassium hydrogen phthalate. The required volumes of sodium hydroxide solution for the three titrations are 10.1 mL, 10.0 mL, and 10.1 mL, respectively. Take the average value of 10.0 mL. The final concentration of the sodium hydroxide solution is: 2.45 * 0.020 / 0.010 = 4.90 mmol / L. Finally, 26.7 mL of NaOH solution is titrated. Therefore, the catalyst acidity is: 4.90 * 0.0246 * 10 = 1.31 mmol / g.

[0160] Example 12: Preparation of glucose from polysaccharide by directed hydrolysis

[0161] Weigh 400mg Fe3O4@SiO2-SO3H and 400mg cellobiose and add them to a 15mL pressure-resistant tube. Then add 10mL of deionized water and a high-temperature resistant magnetic dome. Finally, tighten the cap and fix it inside the coil of the high-frequency electromagnetic induction device, ensuring that the magnetic dome at the bottom is below the coil (to keep the magnetic dome away from the magnetic field and prevent it from being heated).

[0162] Reaction conditions: rotation speed 1000 rpm, reaction time 3 h, magnetic field strength 0.5 T, magnetic field frequency 380 kHz, relay operation set to cycle for 40 s on and 4 s off. After the reaction, the product was detected using HPLC (High Performance Liquid Chromatography), and the yield was calculated using the standard curve method (using glucose as a standard solution).

[0163] The detection conditions were as follows: column: SUGAR-SH1011, column temperature: 30℃, detector: differential refractive index detector (2414RI Detector), mobile phase: 5 mmol / L sulfuric acid, flow rate: 0.6 mL / min.

[0164] In comparison, the operation process was similar to that of Example 12 above, except that the electromagnetic heating method was replaced with traditional oil bath heating at 150°C for 3 hours. The reaction results are shown in Table 9 below:

[0165] Table 9

[0166]

[0167] A comparison of the effect data in Table 9 and Table 1 shows that the magnetic solid acid with a core-shell structure prepared in Example 1 has a better promoting effect on the hydrolysis process of cellobiose.

[0168] Example 13: Preparation of glucose from polysaccharide by directed hydrolysis

[0169] Weigh 400mg Fe3O4@SiO2-SO3H and 400mg soluble starch and add them to a 15mL pressure-resistant tube. Then add 10mL deionized water and a high-temperature resistant magnetic dome. Finally, tighten the cap and fix it inside the coil of the high-frequency electromagnetic induction device, ensuring that the magnetic dome at the bottom is below the coil (to keep the magnetic dome away from the magnetic field and prevent it from being heated).

[0170] Reaction conditions: rotation speed 1000 rpm, reaction time 3 h, magnetic field strength 0.5 T, magnetic field frequency 380 kHz, relay operation set to cycle for 40 s on and 4 s off. After the reaction, the total reducing sugar yield of the reaction solution was determined by the 3,5-dinitrosalicylic acid method, and a standard curve of total reducing sugar was constructed (using cellobiose as the standard solution). The products were detected by HPLC (high performance liquid chromatography), and the yield was calculated using the standard curve method (using glucose as the standard solution).

[0171] The detection conditions were as follows: Total reducing sugar determination equipment: UV-Vis spectrophotometer; cuvettes: quartz cuvettes; detection wavelength: 540 nm; chromatographic column: SUGAR-SH1011; column temperature: 30℃; detector: differential refractive index detector (2414 RI Detector); mobile phase: 5 mmol / L sulfuric acid; flow rate: 0.6 mL / min.

[0172] In comparison, the operation process was similar to that of Example 13 above, except that the electromagnetic heating method was replaced with traditional oil bath heating at a temperature of 150°C for 3 hours. Furthermore, also for comparison, the operation process was similar to that of Example 13 above, except that the reactant was changed to cellulose. The reaction results are shown in Table 10 below:

[0173] Table 10

[0174]

[0175] A comparison of the effect data in Table 10 and Table 2 shows that the magnetic solid acid with a core-shell structure prepared in Example 1 has a better promoting effect on the hydrolysis process of soluble starch and cellulose.

[0176] Example 14: Preparation of glucose from polysaccharide by directed hydrolysis

[0177] Weigh 40g of [BMIM]Cl ionic liquid into a 250mL round-bottom flask, add a little water to dissolve the ionic liquid, and after the solution becomes clear and transparent, perform vacuum rotary evaporation. Once the solution becomes gel-like, add 2g of cellulose and heat and stir at 80℃ for 6 hours. You will see the cellulose dissolve into the [BMIM]Cl, and the solution will become clear and transparent. Then stop heating and quickly add purified water while stirring. Continue stirring until there are no large solid lumps in the solution, and then centrifuge at 10000rpm / min for 10min. The evaporated liquid is recycled as [BMIM]Cl ionic liquid, and the remaining solid is dried in a vacuum oven at 80℃.

[0178] Weigh 400mg Fe3O4@SiO2-SO3H and 400mg of the above-treated cellulose and add them to a 15mL pressure-resistant tube. Then add 10mL of deionized water and a high-temperature resistant magnetic dome. Finally, tighten the cap and fix it inside the coil of the high-frequency electromagnetic induction device, ensuring that the magnetic dome at the bottom is below the coil (to keep the magnetic dome away from the magnetic field and prevent it from being heated).

[0179] Reaction conditions: rotation speed 1000 rpm, reaction time 6 h, magnetic field strength 0.5 T, magnetic field frequency 380 kHz, relay operation set to cycle for 40 s on and 4 s off. After the reaction, the total reducing sugar yield of the reaction solution was determined by the 3,5-dinitrosalicylic acid method, and a standard curve of total reducing sugar was constructed (using cellobiose as the standard solution). The products were detected by HPLC (high performance liquid chromatography), and the yield was calculated using the standard curve method (using glucose as the standard solution).

[0180] The detection conditions were as follows: Total reducing sugar determination equipment: UV-Vis spectrophotometer; cuvettes: quartz cuvettes; detection wavelength: 540 nm; chromatographic column: SUGAR-SH1011; column temperature: 30℃; detector: differential refractive index detector (2414 RI Detector); mobile phase: 5 mmol / L sulfuric acid; flow rate: 0.6 mL / min.

[0181] In comparison, the operation process was similar to that of Example 14, except that the reaction time was changed. The reaction results are shown in Table 11 below:

[0182] Table 11

[0183]

[0184] A comparison of the effect data in Table 11 and Table 3 shows that, for the hydrolysis process of cellulose, the magnetic solid acid with a core-shell structure prepared in Example 1 has a better promoting effect, and has higher selectivity and yield at the same reaction time.

[0185] Example 15: Preparation of glucose from polysaccharide by directed hydrolysis

[0186] Weigh 10g of cotton, pulverize it thoroughly with scissors, then wash it several times with deionized water and dry it thoroughly in an 80℃ vacuum oven.

[0187] Weigh 200g of [BMIM]Cl ionic liquid into a 500mL round-bottom flask, add a little water to dissolve the ionic liquid, and after the solution becomes clear and transparent, perform vacuum rotary evaporation. Once the solution becomes gel-like, add 10g of cotton wool and heat and stir at 80℃ for 6 hours. The cotton wool will dissolve into the [BMIM]Cl, and the solution will become clear and transparent. Then stop heating and quickly add purified water while stirring. Continue stirring until there are no large solid clumps in the solution, and then centrifuge at 10000rpm / min for 10 minutes. The evaporated liquid is recycled as [BMIM]Cl ionic liquid, and the remaining solid is dried in a vacuum oven at 80℃.

[0188] Weigh 400mg Fe3O4@SiO2-SO3H and 400mg of the above-treated cotton and add them to a 15mL pressure-resistant tube. Then add 10mL of deionized water and a high-temperature resistant magnetic dome. Finally, tighten the cap and fix it inside the coil of the high-frequency electromagnetic induction device, ensuring that the magnetic dome at the bottom is below the coil (to keep the magnetic dome away from the magnetic field and prevent it from being heated).

[0189] Reaction conditions: rotation speed 1000 rpm, reaction time 15 h, magnetic field strength 0.5 T, magnetic field frequency 380 kHz, relay operation set to cycle for 40 s on and 4 s off. After the reaction, the total reducing sugar yield of the reaction solution was determined by the 3,5-dinitrosalicylic acid method, and a standard curve of total reducing sugar was constructed (using cellobiose as the standard solution). The products were detected by HPLC (high performance liquid chromatography), and the yield was calculated using the standard curve method (using glucose as the standard solution).

[0190] The detection conditions were as follows: Total reducing sugar determination equipment: UV-Vis spectrophotometer; cuvettes: quartz cuvettes; detection wavelength: 540 nm; chromatographic column: SUGAR-SH 1011; column temperature: 30℃; detector: differential refractive index detector (2414 RI Detector); mobile phase: 5 mmol / L sulfuric acid; flow rate: 0.6 mL / min.

[0191] In comparison, the operation process was similar to that of Example 15 above, except that the electromagnetic heating method was replaced with traditional oil bath heating at a temperature of 150°C for 3 hours. Furthermore, also for comparison, the pretreatment process and reaction were similar to those of Example 15 above, except that the reactant was replaced with paper. The reaction results are shown in Table 12 below:

[0192] Table 12

[0193]

[0194] A comparison of the effect data in Tables 12 and 4 shows that the magnetic solid acid with a core-shell structure prepared in Example 1 has a better promoting effect on the hydrolysis process of cotton and paper, and has higher selectivity and yield at the same reaction time.

[0195] Example 16: A nitrogen-containing carbon nanotube magnetic solid acid catalyst

[0196] 1. Preparation of Co nanoparticles encapsulated in nitrogen-containing carbon nanotubes

[0197] 11.25 g of melamine, 7.5 g of P123, and 5 g of cobalt acetate tetrahydrate [Co(CH3COO)2·4H2O] were weighed and dissolved in 400 mL of deionized water. The solution was stirred at room temperature for 2 h, then heated to 80 °C and stirred for another 30 min. The solvent was then removed by spin-drying, and the solution was dried in a vacuum oven at 80 °C for 12 h. The dried powder was placed in a quartz boat and calcined in a tube furnace under a nitrogen atmosphere, with the temperature increased at 5 °C / min to 700 °C and held for 2 h. After cooling to room temperature, the powder was removed. The resulting solid powder was stirred in a 1.0 M HCl solution at 80 °C for 12 h to completely remove unencapsulated metal nanoparticles. The filtered and washed black solid powder was vacuum dried overnight, and the resulting solid was labeled Co@NC.

[0198] 2. Sulfonation of Co nanoparticles encapsulated in nitrogen-containing carbon nanotubes

[0199] Take 6g of Co@NC obtained in step 1 and add it to a 500mL round-bottom flask, along with 300mL of dichloromethane. Then, slowly add 7.5mL of chlorosulfonic acid dropwise over 15min. After the addition is complete, stir the mixture at room temperature for 48h. After the reaction is complete, filter the mixture and wash it several times with dichloromethane. Then, dry it in a vacuum drying oven at 80℃ for 12h. The resulting black solid powder is labeled as Co@NC-SO3H.

[0200] Acidity determination (acid-base titration): 0.1 g of the magnetic solid acid catalyst prepared above was added to 20 mL of a 2 mol / L NaCl solution and stirred at room temperature for 24 h. The solution was then titrated with NaOH (250 mL water + 50 mg NaOH). Because solid sodium hydroxide is highly susceptible to moisture in air, simply weighing the solution to prepare it is insufficient to determine the true concentration of sodium hydroxide. Therefore, potassium hydrogen phthalate was used to titrate the sodium hydroxide concentration.

[0201] Sodium hydroxide concentration determination: Weigh 50 mg of potassium hydrogen phthalate solid and dissolve it in 100 mL of water (concentration 2.45 mmol / L). Then, titrate the known concentration of potassium hydrogen phthalate with the prepared sodium hydroxide solution. Titrate three times and take the average value. Each titration uses 20 mL of potassium hydrogen phthalate. The required volumes of sodium hydroxide solution for the three titrations are 9.8 mL, 9.9 mL, and 9.9 mL, respectively. Take the average value of 9.9 mL. The final concentration of the sodium hydroxide solution is: 2.45 * 0.020 / 0.0099 = 4.95 mmol / L. Finally, 36.9 mL of NaOH solution is titrated. Therefore, the catalyst acidity is: 4.95 * 0.0369 * 10 = 1.83 mmol / g.

[0202] Example 17: Preparation of glucose from polysaccharide by directed hydrolysis

[0203] Weigh 400mg Co@NC-SO3H and 400mg cellobiose and add them to a 15mL pressure-resistant tube. Then add 10mL of deionized water and a high-temperature resistant magnetic dome. Finally, tighten the cap and fix it inside the coil of the high-frequency electromagnetic induction device, ensuring that the magnetic dome at the bottom is below the coil (to keep the magnetic dome away from the magnetic field and prevent it from being heated).

[0204] Reaction conditions: rotation speed 1000 rpm, reaction time 3 h, magnetic field strength 0.5 T, magnetic field frequency 380 kHz, relay operation set to cycle for 40 s on and 4 s off. After the reaction, the product was detected using HPLC (High Performance Liquid Chromatography), and the yield was calculated using the standard curve method (using glucose as a standard solution).

[0205] The detection conditions were as follows: column: SUGAR-SH1011, column temperature: 30℃, detector: differential refractive index detector (2414RI Detector), mobile phase: 5 mmol / L sulfuric acid, flow rate: 0.6 mL / min.

[0206] In comparison, the operation process was similar to that of Example 17 above, except that the electromagnetic heating method was replaced with traditional oil bath heating at 150°C for 3 hours. The reaction results are shown in Table 13 below:

[0207] Table 13

[0208]

[0209] A comparison of the effect data in Table 13 and Table 1 shows that the magnetic solid acid with a core-shell structure prepared in Example 1 has a better promoting effect on the hydrolysis process of cellobiose, and has higher selectivity and yield at the same reaction time.

[0210] Example 18: Preparation of glucose from polysaccharide by directed hydrolysis

[0211] Weigh 400mg Co@NC-SO3H and 400mg soluble starch and add them to a 15mL pressure-resistant tube. Then add 10mL of deionized water and a high-temperature resistant magnetic dome. Finally, tighten the cap and fix it inside the coil of the high-frequency electromagnetic induction device, ensuring that the magnetic dome at the bottom is below the coil (to keep the magnetic dome away from the magnetic field and prevent it from being heated).

[0212] Reaction conditions: rotation speed 1000 rpm, reaction time 3 h, magnetic field strength 0.5 T, magnetic field frequency 380 kHz, relay operation set to cycle for 40 s on and 4 s off. After the reaction, the total reducing sugar yield of the reaction solution was determined by the 3,5-dinitrosalicylic acid method, and a standard curve of total reducing sugar was constructed (using cellobiose as the standard solution). The products were detected by HPLC (high performance liquid chromatography), and the yield was calculated using the standard curve method (using glucose as the standard solution).

[0213] The detection conditions were as follows: Total reducing sugar determination equipment: UV-Vis spectrophotometer; cuvettes: quartz cuvettes; detection wavelength: 540 nm; chromatographic column: SUGAR-SH1011; column temperature: 30℃; detector: differential refractive index detector (2414 RI Detector); mobile phase: 5 mmol / L sulfuric acid; flow rate: 0.6 mL / min.

[0214] In comparison, the operation process was similar to that of Example 18 above, except that the electromagnetic heating method was replaced with traditional oil bath heating at 150°C for 3 hours. Furthermore, also for comparison, the operation process was similar to that of Example 18 above, except that the reactant was changed to cellulose. The reaction results are shown in Table 14 below:

[0215] Table 14

[0216]

[0217] A comparison of the effect data in Table 14 and Table 2 shows that the magnetic solid acid with a core-shell structure prepared in Example 1 has a better promoting effect on the hydrolysis process of soluble starch and cellulose, and has higher selectivity and yield at the same reaction time.

[0218] Example 19: Preparation of glucose from polysaccharide by directed hydrolysis

[0219] Weigh 40g of [BMIM]Cl ionic liquid into a 250mL round-bottom flask, add a little water to dissolve the ionic liquid, and after the solution becomes clear and transparent, perform vacuum rotary evaporation. Once the solution becomes gel-like, add 2g of cellulose and heat and stir at 80℃ for 6 hours. You will see the cellulose dissolve into the [BMIM]Cl, and the solution will become clear and transparent. Then stop heating and quickly add purified water while stirring. Continue stirring until there are no large solid lumps in the solution, then centrifuge at 10000rpm / min for 10min. The evaporated liquid is recycled as [BMIM]Cl ionic liquid, and the remaining solid is dried in a vacuum oven at 80℃.

[0220] Weigh 400mg Co@NC-SO3H and 400mg of the above-treated cellulose and add them to a 15mL pressure-resistant tube. Then add 10mL of deionized water and a high-temperature resistant magnetic dome. Finally, tighten the cap and fix it inside the coil of the high-frequency electromagnetic induction device, ensuring that the magnetic dome at the bottom is below the coil (to keep the magnetic dome away from the magnetic field and prevent it from being heated).

[0221] Reaction conditions: rotation speed 1000 rpm, reaction time 6 h, magnetic field strength 0.5 T, magnetic field frequency 380 kHz, relay operation set to cycle for 40 s on and 4 s off. After the reaction, the total reducing sugar yield of the reaction solution was determined by the 3,5-dinitrosalicylic acid method, and a standard curve of total reducing sugar was constructed (using cellobiose as the standard solution). The products were detected by HPLC (high performance liquid chromatography), and the yield was calculated using the standard curve method (using glucose as the standard solution).

[0222] The detection conditions were as follows: Total reducing sugar determination equipment: UV-Vis spectrophotometer; cuvettes: quartz cuvettes; detection wavelength: 540 nm; chromatographic column: SUGAR-SH 1011; column temperature: 30℃; detector: differential refractive index detector (2414 RI Detector); mobile phase: 5 mmol / L sulfuric acid; flow rate: 0.6 mL / min.

[0223] In comparison, the operation process was similar to that of Example 19, except that the reaction time was changed. The reaction results are shown in Table 15 below:

[0224] Table 15

[0225]

[0226] A comparison of the effect data in Table 15 and Table 3 shows that, for the hydrolysis process of cellulose, the magnetic solid acid with a core-shell structure prepared in Example 1 has a better promoting effect, and has higher selectivity and yield at the same reaction time.

[0227] Example 20: Preparation of glucose from polysaccharide by directed hydrolysis

[0228] Weigh 10g of cotton, pulverize it thoroughly with scissors, then wash it several times with deionized water and dry it thoroughly in an 80℃ vacuum oven.

[0229] Weigh 200g of [BMIM]Cl ionic liquid into a 500mL round-bottom flask, add a little water to dissolve the ionic liquid, and after the solution becomes clear and transparent, perform vacuum rotary evaporation. Once the solution becomes gel-like, add 10g of cotton wool and heat and stir at 80℃ for 6 hours. The cotton wool will dissolve into the [BMIM]Cl, and the solution will become clear and transparent. Then stop heating and quickly add purified water while stirring. Continue stirring until there are no large solid clumps in the solution, and then centrifuge at 10000rpm / min for 10 minutes. The evaporated liquid is recycled as [BMIM]Cl ionic liquid, and the remaining solid is dried in a vacuum oven at 80℃.

[0230] Weigh 400mg Co@NC-SO3H and 400mg of the above-treated cotton and add them to a 15mL pressure-resistant tube. Then add 10mL of deionized water and a high-temperature resistant magnetic dome. Finally, tighten the cap and fix it inside the coil of the high-frequency electromagnetic induction device, ensuring that the magnetic dome at the bottom is below the coil (to keep the magnetic dome away from the magnetic field and prevent it from being heated).

[0231] Reaction conditions: rotation speed 1000 rpm, reaction time 15 h, magnetic field strength 0.5 T, magnetic field frequency 380 kHz, relay operation set to cycle for 40 s on and 4 s off. After the reaction, the total reducing sugar yield of the reaction solution was determined by the 3,5-dinitrosalicylic acid method, and a standard curve of total reducing sugar was constructed (using cellobiose as the standard solution). The products were detected by HPLC (high performance liquid chromatography), and the yield was calculated using the standard curve method (using glucose as the standard solution).

[0232] The detection conditions were as follows: Total reducing sugar determination equipment: UV-Vis spectrophotometer; cuvettes: quartz cuvettes; detection wavelength: 540 nm; chromatographic column: SUGAR-SH 1011; column temperature: 30℃; detector: differential refractive index detector (2414 RI Detector); mobile phase: 5 mmol / L sulfuric acid; flow rate: 0.6 mL / min.

[0233] In comparison, the operation process was similar to that of Example 20 above, except that the electromagnetic heating method was replaced with traditional oil bath heating at a temperature of 150°C for 3 hours. Furthermore, also for comparison, the pretreatment process and reaction were similar to those of Example 20 above, except that the reactants were replaced with paper. The reaction results are shown in Table 16 below:

[0234] Table 16

[0235]

[0236] A comparison of the effect data in Table 16 and Table 4 shows that, for the hydrolysis process of cotton and paper, the magnetic solid acid with a core-shell structure prepared in Example 1 has a better promoting effect, and exhibits higher selectivity and yield at the same reaction time.

[0237] Example 21: Preparation of magnetic solid acids with core-shell structure

[0238] 1. Preparation of Ni@Gr precursor

[0239] 10 g of Ni(CHOO)₂·2H₂O was weighed and placed in a quartz boat. The quartz boat was then placed in a quartz tube, and the temperature was raised to 250 °C at a rate of 5 °C / min under an H₂ / Ar (10% H₂ and 90% Ar) gas flow, and held for 1 h. The temperature was then increased from 250 °C to 800 °C at a rate of 5 °C / min and held for 30 min, followed by the introduction of CH₄ gas for 30 min. After the reaction was complete, the solid was allowed to cool to room temperature, and then the solid in the quartz boat was removed, ground, and sieved (100 mesh) and labeled as Ni@Gr for further use.

[0240] 2. Preparation of Ni@Gr@C precursor

[0241] Weigh out 30g of glucose monohydrate (C6H) 12 Ni@Gr prepared in step 1 was dissolved in 300 ml of anhydrous ethanol-water solution (volume ratio of anhydrous ethanol:water = 2:1). Then, 3 g of Ni@Gr prepared in step 1 was added, and the mixture was ultrasonically dispersed. The mixture was then transferred to a hydrothermal reactor and hydrothermally reacted at 190 °C for 12 h in a homogeneous reactor. After the reaction was completed, the solid was evaporated using a rotary evaporator and then vacuum dried at 80 °C for 12 h in a vacuum drying oven. The dried solid was then calcined in a tube furnace under the conditions of heating to 600 °C at a rate of 5 °C / min and holding for 2 h. After cooling to room temperature, the solid was removed, ground, and passed through a 100-mesh sieve. This solid was denoted as Ni@Gr@C.

[0242] 3. Introduction of adsorption groups

[0243] Take 6g of Ni@Gr@C and add it to 60mL of 10% nitric acid solution. Transfer the mixture to a 350mL pressure-resistant tube and react it in an oil bath at 80℃ for 4 hours under an argon atmosphere. Then wash with deionized water and centrifuge until the washing solution is neutral.

[0244] The 10% nitric acid used in this step is prepared from a 67% nitric acid standard solution.

[0245] The material obtained in step 3 has a surface activated by nitric acid and modified with some weakly acidic adsorption groups of -OH and -COOH compared to that in step 2.

[0246] 4. Preparation of Ni@Gr@C-SO3H catalyst

[0247] The dried catalyst precursor from step 3 was added to a 350 mL pressure-resistant tube, along with 60 mL of concentrated sulfuric acid. Under argon protection, the mixture was stirred and reacted at 200 °C for 24 h. After the reaction was completed, the mixture was washed with deionized water and centrifuged until the washing liquid was neutral, yielding a magnetic solid acid Ni@Gr@C-SO3H with a core-shell structure.

[0248] The concentrated sulfuric acid used in this step is a 98% concentrated sulfuric acid standard solution.

[0249] Acidity determination (acid-base titration): 0.1 g of magnetic solid acid catalyst was added to 20 mL of 2 mol / L NaCl solution and stirred at room temperature for 24 h. The solution was then titrated with NaOH (250 mL water + 50 mg NaOH). Because solid sodium hydroxide is highly susceptible to moisture in air, simply weighing and preparing the solution cannot determine the true concentration of sodium hydroxide. Therefore, potassium hydrogen phthalate was used to titrate the sodium hydroxide concentration.

[0250] Sodium hydroxide concentration determination: Weigh 50 mg of potassium hydrogen phthalate solid and dissolve it in 100 mL of water (concentration 2.45 mmol / L). Then, titrate the known concentration of potassium hydrogen phthalate with the prepared sodium hydroxide solution. Titrate three times and take the average value. Each titration uses 20 mL of potassium hydrogen phthalate. The required volumes of sodium hydroxide solution for the three titrations are 9.5 mL, 9.5 mL, and 9.5 mL, respectively. Take the average value of 9.5 mL. The final concentration of the sodium hydroxide solution is: 2.45 * 0.020 / 0.00950 = 5.16 mmol / L. Finally, 27.5 mL of NaOH solution is titrated. Therefore, the catalyst acidity is: 5.16 * 0.0275 * 10 = 1.42 mmol / g. Example 22: Directed hydrolysis of polysaccharides to prepare glucose.

[0251] Weigh 200mg Ni@Gr@C-SO3H and 200mg cellobiose and add them to a 15mL pressure-resistant tube. Then add 8mL of deionized water and a high-temperature resistant magnetic dome. Finally, tighten the cap and fix it inside the coil of a high-frequency electromagnetic induction device, ensuring that the magnetic dome at the bottom is below the coil (to keep the magnetic dome away from the magnetic field and prevent it from being heated).

[0252] Reaction conditions: rotation speed 1000 rpm, reaction time 3 h, magnetic field strength 0.8 T, magnetic field frequency 470 kHz, relay operation set to cycle for 40 s on and 4 s off. After the reaction, the product was detected using HPLC (High Performance Liquid Chromatography), and the yield was calculated using the standard curve method (using glucose as a standard solution).

[0253] The detection conditions were as follows: column: SUGAR-SH 1011, column temperature: 30℃, detector: differential refractive index detector (2414RI Detector), mobile phase: 5 mmol / L sulfuric acid, flow rate: 0.6 mL / min.

[0254] In comparison, the operation process was similar to that of Example 22 above, except that the electromagnetic heating method was replaced with traditional oil bath heating at 150°C for 3 hours. The reaction results are shown in Table 17 below:

[0255] Table 17

[0256]

[0257] A comparison of the effect data in Table 17 and Table 1 shows that the magnetic solid acid with a core-shell structure prepared in Example 1 has a better promoting effect on the hydrolysis process of cellobiose, and has higher selectivity and yield at the same reaction time.

[0258] Example 23: Preparation of glucose from polysaccharide by directed hydrolysis

[0259] Weigh 200mg Ni@Gr@C-SO3H and 200mg soluble starch and add them to a 15mL pressure-resistant tube. Then add 8mL of deionized water and a high-temperature resistant magnetic dome. Finally, tighten the cap and fix it inside the coil of the high-frequency electromagnetic induction device, ensuring that the magnetic dome at the bottom is below the coil (to keep the magnetic dome away from the magnetic field and prevent it from being heated).

[0260] Reaction conditions: rotation speed 1000 rpm, reaction time 3 h, magnetic field strength 0.8 T, magnetic field frequency 470 kHz, relay operation set to cycle for 40 s on and 4 s off. After the reaction, the total reducing sugar yield of the reaction solution was determined by the 3,5-dinitrosalicylic acid method, and a standard curve of total reducing sugar was constructed (using cellobiose as the standard solution). The products were detected by HPLC (high performance liquid chromatography), and the yield was calculated using the standard curve method (using glucose as the standard solution).

[0261] The detection conditions were as follows: Total reducing sugar determination equipment: UV-Vis spectrophotometer; cuvettes: quartz cuvettes; detection wavelength: 540 nm; chromatographic column: SUGAR-SH 1011; column temperature: 30℃; detector: differential refractive index detector (2414 RI Detector); mobile phase: 5 mmol / L sulfuric acid; flow rate: 0.6 mL / min.

[0262] In comparison, the operation process was similar to that of Example 23 above, except that the electromagnetic heating method was replaced with traditional oil bath heating at 150°C for 3 hours. Furthermore, also for comparison, the operation process was similar to that of Example 23 above, except that the reactant was changed to cellulose. The reaction results are shown in Table 18 below:

[0263] Table 18

[0264]

[0265] A comparison of the effect data in Table 18 and Table 2 shows that the magnetic solid acid with a core-shell structure prepared in Example 1 has a better promoting effect on the hydrolysis process of soluble starch and cellulose.

[0266] Example 24: Preparation of glucose from polysaccharide by directed hydrolysis

[0267] Weigh 40g of [BMIM]Cl ionic liquid into a 250mL round-bottom flask, add a little water to dissolve the ionic liquid, and after the solution becomes clear and transparent, perform vacuum rotary evaporation. Once the solution becomes gel-like, add 2g of cellulose and heat and stir at 80℃ for 6 hours. You will see the cellulose dissolve into the [BMIM]Cl, and the solution will become clear and transparent. Then stop heating and quickly add purified water while stirring. Continue stirring until there are no large solid lumps in the solution, then centrifuge at 10000rpm / min for 10min. The evaporated liquid is recycled as [BMIM]Cl ionic liquid, and the remaining solid is dried in a vacuum oven at 80℃.

[0268] Weigh 200mg Ni@Gr@C-SO3H and 200mg of the above-treated cellulose and add them to a 15mL pressure-resistant tube. Then add 8mL of deionized water and a high-temperature resistant magnetic dome. Finally, tighten the cap and fix it inside the coil of the high-frequency electromagnetic induction device, ensuring that the magnetic dome at the bottom is below the coil (to keep the magnetic dome away from the magnetic field and prevent it from being heated).

[0269] Reaction conditions: rotation speed 1000 rpm, reaction time 6 h, magnetic field strength 0.8 T, magnetic field frequency 470 kHz, relay operation set to cycle for 40 s on and 4 s off. After the reaction, the total reducing sugar yield of the reaction solution was determined by the 3,5-dinitrosalicylic acid method, and a standard curve of total reducing sugar was constructed (using cellobiose as the standard solution). The products were detected by HPLC (high performance liquid chromatography), and the yield was calculated using the standard curve method (using glucose as the standard solution).

[0270] The detection conditions were as follows: Total reducing sugar determination equipment: UV-Vis spectrophotometer; cuvettes: quartz cuvettes; detection wavelength: 540 nm; chromatographic column: SUGAR-SH 1011; column temperature: 30℃; detector: differential refractive index detector (2414 RI Detector); mobile phase: 5 mmol / L sulfuric acid; flow rate: 0.6 mL / min.

[0271] In comparison, the operation process was similar to that of Example 23, except that the reaction time was changed. The reaction results are shown in Table 19 below:

[0272] Table 19

[0273]

[0274] A comparison of the effect data in Table 19 and Table 3 shows that, for the hydrolysis process of cellulose, the magnetic solid acid with a core-shell structure prepared in Example 1 has a better promoting effect, and has higher selectivity and yield at the same reaction time.

[0275] Example 25: Preparation of glucose from polysaccharide by directed hydrolysis

[0276] Weigh 10g of cotton, pulverize it thoroughly with scissors, then wash it several times with deionized water and dry it thoroughly in an 80℃ vacuum oven.

[0277] Weigh 200g of [BMIM]Cl ionic liquid into a 500mL round-bottom flask, add a little water to dissolve the ionic liquid, and after the solution becomes clear and transparent, perform vacuum rotary evaporation. Once the solution becomes gel-like, add 10g of cotton wool and heat and stir at 80℃ for 6 hours. The cotton wool will dissolve into the [BMIM]Cl, and the solution will become clear and transparent. Then stop heating and quickly add purified water while stirring. Continue stirring until there are no large solid clumps in the solution, and then centrifuge at 10000rpm / min for 10 minutes. The evaporated liquid is recycled as [BMIM]Cl ionic liquid, and the remaining solid is dried in a vacuum oven at 80℃.

[0278] Weigh 200mg Ni@Gr@C-SO3H and 200mg of the above-treated cotton and add them to a 15mL pressure-resistant tube. Then add 8mL of deionized water and a high-temperature resistant magnetic dome. Finally, tighten the cap and fix it inside the coil of the high-frequency electromagnetic induction device, ensuring that the magnetic dome at the bottom is below the coil (to keep the magnetic dome away from the magnetic field and prevent it from being heated).

[0279] Reaction conditions: rotation speed 1000 rpm, reaction time 15 h, magnetic field strength 0.8 T, magnetic field frequency 470 kHz, relay operation set to cycle for 40 s on and 4 s off. After the reaction, the total reducing sugar yield of the reaction solution was determined by the 3,5-dinitrosalicylic acid method, and a standard curve of total reducing sugar was constructed (using cellobiose as the standard solution). The products were detected by HPLC (high performance liquid chromatography), and the yield was calculated using the standard curve method (using glucose as the standard solution).

[0280] The detection conditions were as follows: Total reducing sugar determination equipment: UV-Vis spectrophotometer; cuvettes: quartz cuvettes; detection wavelength: 540 nm; chromatographic column: SUGAR-SH 1011; column temperature: 30℃; detector: differential refractive index detector (2414 RI Detector); mobile phase: 5 mmol / L sulfuric acid; flow rate: 0.6 mL / min.

[0281] In comparison, the operation process was similar to that of Example 25 above, except that the electromagnetic heating method was replaced with traditional oil bath heating at a temperature of 150°C for 3 hours. Furthermore, also for comparison, the pretreatment process and reaction were similar to those of Example 25 above, except that the reactants were replaced with paper. The reaction results are shown in Table 20 below:

[0282] Table 20

[0283]

[0284] A comparison of the effect data in Tables 20 and 4 shows that the magnetic solid acid with a core-shell structure prepared in Example 1 has a better promoting effect on the hydrolysis process of cotton and paper, and has higher selectivity and yield at the same reaction time.

[0285] Example 26: Preparation of magnetic solid acids with core-shell structures

[0286] 1. Preparation of FeCo magnetic nanoparticles

[0287] First, 14 g of ferrous sulfate heptahydrate (FeSO4·7H2O), 12 g of cobalt dichloride hexahydrate (CoCl2·6H2O), 30 g of PEG-6000, and 25 mL of cyclohexane were added to a flask containing 750 mL of water. Under an argon atmosphere, the mixture was mechanically stirred and sonicated for 1 hour. Then, at 78 °C, 300 mL of an 80 wt% hydrazine hydrate solution containing 8 g of NaOH was added dropwise. The reaction temperature was maintained for 30 min, and the product was then allowed to cool naturally to room temperature. Finally, the product was collected using a magnet, washed repeatedly with deionized water and ethanol, and dried under vacuum at 60 °C.

[0288] 2. Preparation of FeCo@C nanoparticle precursors

[0289] Weigh out 60g of glucose monohydrate (C6H) 12 O6·H2O) was dissolved in 300 mL of deionized water, and then 3 g of FeCo prepared in step 1 was added. The mixture was ultrasonically dispersed and then transferred to a hydrothermal reactor. The mixture was then hydrothermally reacted at 180 °C for 18 h in a homogeneous reactor. After the reaction was completed, the solid was evaporated using a rotary evaporator and then vacuum dried at 80 °C for 12 h in a vacuum drying oven. The dried solid was then calcined in a tube furnace under the conditions of heating to 700 °C at a rate of 5 °C / min and holding for 2 h. After cooling to room temperature, the solid was removed, ground, and passed through a 100-mesh sieve. This solid was denoted as FeCo@C.

[0290] 3. Introduction of adsorption groups

[0291] Take 6g of FeCo@C and add it to 60mL of 10% nitric acid solution. Transfer the mixture to a 350mL pressure-resistant tube and react it in an oil bath at 80℃ for 4h under argon atmosphere protection. Then wash with deionized water and centrifuge until the washing solution is neutral.

[0292] The 10% nitric acid used in this step is prepared from a 67% nitric acid standard solution.

[0293] The material obtained in step 3 has a surface activated by nitric acid and modified with some weakly acidic adsorption groups of -OH and -COOH compared to that in step 2.

[0294] 4. Preparation of FeCo@C-SO3H catalyst

[0295] The dried catalyst precursor from step 3 was added to a 350 mL pressure-resistant tube, along with 60 mL of concentrated sulfuric acid. Under argon protection, the mixture was stirred and reacted at 200 °C for 24 h. After the reaction was completed, the mixture was washed with deionized water and centrifuged until the washing liquid was neutral to obtain the magnetic solid acid FeCo@C-SO3H with a core-shell structure.

[0296] The concentrated sulfuric acid used in this step is a 98% concentrated sulfuric acid standard solution.

[0297] Acidity determination (acid-base titration): 0.1 g of magnetic solid acid catalyst was added to 20 mL of 2 mol / L NaCl solution and stirred at room temperature for 24 h. The solution was then titrated with NaOH (250 mL water + 50 mg NaOH). Because solid sodium hydroxide is highly susceptible to moisture in air, simply weighing and preparing the solution cannot determine the true concentration of sodium hydroxide. Therefore, potassium hydrogen phthalate was used to titrate the sodium hydroxide concentration.

[0298] Sodium hydroxide concentration determination: Weigh 50 mg of potassium hydrogen phthalate solid and dissolve it in 100 mL of water (concentration 2.45 mmol / L). Then, titrate the known concentration of potassium hydrogen phthalate with the prepared sodium hydroxide solution. Titrate three times and take the average value. Each titration uses 20 mL of potassium hydrogen phthalate. The required volumes of sodium hydroxide solution for the three titrations are 9.6 mL, 9.5 mL, and 9.6 mL, respectively. Take the average value of 9.57 mL. The final concentration of the sodium hydroxide solution is: 2.45 * 0.020 / 0.00957 = 5.12 mmol / L. Finally, 20.8 mL of NaOH solution is titrated. Therefore, the catalyst acidity is: 5.16 * 0.0208 * 10 = 1.07 mmol / g.

[0299] Example 27: Preparation of glucose from polysaccharide by directed hydrolysis

[0300] Weigh 200mg FeCo@C-SO3H and 200mg cellobiose and add them to a 15mL Shrek tube. Then add 8mL of deionized water and a high-temperature resistant magnetic dome. Finally, tighten the cap and fix it inside the coil of a high-frequency electromagnetic induction device, ensuring that the magnetic dome at the bottom is below the coil (to keep the magnetic dome away from the magnetic field and prevent it from being heated).

[0301] Reaction conditions: rotation speed 1000 rpm, reaction time 3 h, magnetic field strength 0.8 T, magnetic field frequency 470 kHz, relay operation set to cycle for 40 s on and 4 s off. After the reaction, the product was detected using HPLC (High Performance Liquid Chromatography), and the yield was calculated using the standard curve method (using glucose as a standard solution).

[0302] The detection conditions were as follows: column: SUGAR-SH 1011, column temperature: 30℃, detector: differential refractive index detector (2414RI Detector), mobile phase: 5 mmol / L sulfuric acid, flow rate: 0.6 mL / min.

[0303] In comparison, the operation process was similar to that of Example 27 above, except that the electromagnetic heating method was replaced with traditional oil bath heating at 150°C for 3 hours. The reaction results are shown in Table 21 below:

[0304] Table 21

[0305]

[0306] A comparison of the effect data in Table 21 and Table 1 shows that the magnetic solid acid with a core-shell structure prepared in Example 1 has a better promoting effect on the hydrolysis process of cellobiose, and has higher selectivity and yield at the same reaction time.

[0307] Example 28: Preparation of glucose from polysaccharide by directed hydrolysis

[0308] Weigh 200mg FeCo@C-SO3H and 200mg soluble starch into a 15mL Shrek tube, then add 8mL deionized water and a high-temperature resistant magnetic dome. Finally, tighten the cap and fix it inside the coil of the high-frequency electromagnetic induction device, ensuring that the magnetic dome at the bottom is below the coil (to keep the magnetic dome away from the magnetic field and prevent it from being heated).

[0309] Reaction conditions: rotation speed 1000 rpm, reaction time 3 h, magnetic field strength 0.8 T, magnetic field frequency 470 kHz, relay operation set to cycle for 40 s on and 4 s off. After the reaction, the total reducing sugar yield of the reaction solution was determined by the 3,5-dinitrosalicylic acid method, and a standard curve of total reducing sugar was constructed (using cellobiose as the standard solution). The products were detected by HPLC (high performance liquid chromatography), and the yield was calculated using the standard curve method (using glucose as the standard solution).

[0310] The detection conditions were as follows: Total reducing sugar determination equipment: UV-Vis spectrophotometer; cuvettes: quartz cuvettes; detection wavelength: 540 nm; chromatographic column: SUGAR-SH 1011; column temperature: 30℃; detector: differential refractive index detector (2414 RI Detector); mobile phase: 5 mmol / L sulfuric acid; flow rate: 0.6 mL / min.

[0311] In comparison, the operation process was similar to that of Example 28 above, except that the electromagnetic heating method was replaced with traditional oil bath heating at 150°C for 3 hours. Furthermore, also for comparison, the operation process was similar to that of Example 28 above, except that the reactant was changed to cellulose. The reaction results are shown in Table 22 below:

[0312] Table 22

[0313]

[0314] A comparison of the effect data in Table 22 and Table 2 shows that the magnetic solid acid with a core-shell structure prepared in Example 1 has a better promoting effect on the hydrolysis process of soluble starch and cellulose.

[0315] Example 29: Preparation of glucose from polysaccharide by directed hydrolysis

[0316] Weigh 40g of [BMIM]Cl ionic liquid into a 250mL round-bottom flask, add a little water to dissolve the ionic liquid, and after the solution becomes clear and transparent, perform vacuum rotary evaporation. Once the solution becomes gel-like, add 2g of cellulose and heat and stir at 80℃ for 6 hours. You will see the cellulose dissolve into the [BMIM]Cl, and the solution will become clear and transparent. Then stop heating and quickly add purified water while stirring. Continue stirring until there are no large solid lumps in the solution, then centrifuge at 10000rpm / min for 10min. The evaporated liquid is recycled as [BMIM]Cl ionic liquid, and the remaining solid is dried in a vacuum oven at 80℃.

[0317] Weigh 200mg FeCo@C-SO3H and 200mg of the above-treated cellulose and add them to a 15mL Shrek tube. Then add 8mL of deionized water and a high-temperature resistant magnetic dome. Finally, tighten the cap and fix it inside the coil of the high-frequency electromagnetic induction device, ensuring that the magnetic dome at the bottom is below the coil (to keep the magnetic dome away from the magnetic field and prevent it from being heated).

[0318] Reaction conditions: rotation speed 1000 rpm, reaction time 6 h, magnetic field strength 0.8 T, magnetic field frequency 470 kHz, relay operation set to cycle for 40 s on and 4 s off. After the reaction, the total reducing sugar yield of the reaction solution was determined by the 3,5-dinitrosalicylic acid method, and a standard curve of total reducing sugar was constructed (using cellobiose as the standard solution). The products were detected by HPLC (high performance liquid chromatography), and the yield was calculated using the standard curve method (using glucose as the standard solution).

[0319] The detection conditions were as follows: Total reducing sugar determination equipment: UV-Vis spectrophotometer; cuvettes: quartz cuvettes; detection wavelength: 540 nm; chromatographic column: SUGAR-SH 1011; column temperature: 30℃; detector: differential refractive index detector (2414 RI Detector); mobile phase: 5 mmol / L sulfuric acid; flow rate: 0.6 mL / min.

[0320] In comparison, the operation process was similar to that of Example 29, except that the reaction time was changed. The reaction results are shown in Table 23 below:

[0321] Table 23

[0322]

[0323] A comparison of the effect data in Tables 23 and 3 shows that, for the hydrolysis process of cellulose, the magnetic solid acid with a core-shell structure prepared in Example 1 has a better promoting effect, and exhibits higher selectivity and yield at the same reaction time.

[0324] Example 30: Preparation of glucose from polysaccharide by directed hydrolysis

[0325] Weigh 10g of cotton, pulverize it thoroughly with scissors, then wash it several times with deionized water and dry it thoroughly in an 80℃ vacuum oven.

[0326] Weigh 200g of [BMIM]Cl ionic liquid into a 500mL round-bottom flask, add a little water to dissolve the ionic liquid, and after the solution becomes clear and transparent, perform vacuum rotary evaporation. Once the solution becomes gel-like, add 10g of cotton wool and heat and stir at 80℃ for 6 hours. The cotton wool will dissolve into the [BMIM]Cl, and the solution will become clear and transparent. Then stop heating and quickly add purified water while stirring. Continue stirring until there are no large solid clumps in the solution, and then centrifuge at 10000rpm / min for 10 minutes. The evaporated liquid is recycled as [BMIM]Cl ionic liquid, and the remaining solid is dried in a vacuum oven at 80℃.

[0327] Weigh 200mg FeCo@C-SO3H and 200mg of the above-treated cotton and add them to a 15mL Shrek tube. Then add 8mL of deionized water and a high-temperature resistant magnetic dome. Finally, tighten the cap and fix it inside the coil of the high-frequency electromagnetic induction device, ensuring that the magnetic dome at the bottom is below the coil (to keep the magnetic dome away from the magnetic field and prevent it from being heated).

[0328] Reaction conditions: rotation speed 1000 rpm, reaction time 15 h, magnetic field strength 0.8 T, magnetic field frequency 470 kHz, relay operation set to cycle for 40 s on and 4 s off. After the reaction, the total reducing sugar yield of the reaction solution was determined by the 3,5-dinitrosalicylic acid method, and a standard curve of total reducing sugar was constructed (using cellobiose as the standard solution). The products were detected by HPLC (high performance liquid chromatography), and the yield was calculated using the standard curve method (using glucose as the standard solution).

[0329] The detection conditions were as follows: Total reducing sugar determination equipment: UV-Vis spectrophotometer; cuvettes: quartz cuvettes; detection wavelength: 540 nm; chromatographic column: SUGAR-SH 1011; column temperature: 30℃; detector: differential refractive index detector (2414 RI Detector); mobile phase: 5 mmol / L sulfuric acid; flow rate: 0.6 mL / min.

[0330] In comparison, the operation process was similar to that of Example 30 above, except that the electromagnetic heating method was replaced with traditional oil bath heating at a temperature of 150°C for 3 hours. Furthermore, also for comparison, the pretreatment process and reaction were similar to those of Example 30 above, except that the reactants were replaced with paper. The reaction results are shown in Table 24 below:

[0331] Table 24

[0332]

[0333] A comparison of the effect data in Tables 24 and 4 shows that the magnetic solid acid with a core-shell structure prepared in Example 1 has a better promoting effect on the hydrolysis process of cotton and paper, and has higher selectivity and yield at the same reaction time.

[0334] Example 31: Hydrolysis of cellulose into glucose under different frequency variations

[0335] Before the reaction, the raw materials need to be processed. The cotton and paper we use are common biomass raw materials in daily life, and they need to be processed before they can be used in the reaction. The usual steps include crushing, washing, drying, and ionic liquid pretreatment. The specific processing flow is as follows: Weigh a certain amount of cotton / paper, crush it thoroughly with scissors, wash it three times with pure water, and then vacuum dry it overnight. Then, use the same method as for microcrystalline cellulose to perform ionic liquid pretreatment. Weigh 40g of [BMIM]Cl ionic liquid and put it into a 250mL round-bottom flask. Add a little water to dissolve the ionic liquid. After the solution is clear and transparent, vacuum rotary evaporate it. After rotary evaporation until it becomes gelatinous, add 2g of cotton / paper. Heat and stir at 80℃ for 6 hours. You can see that the cellulose is incorporated into [BMIM]Cl and the solution is clear and transparent. Then, stop heating and quickly add pure water while stirring. Continue stirring until there are no large solid colloids in the solution. Then, centrifuge at 10000rpm / min for 10min. The evaporated liquid is vacuum evaporated to obtain [BMIM]Cl ionic liquid for recycling. The remaining solid is dried in a vacuum oven at 80°C to obtain the processed cotton / paper raw material.

[0336] Weigh 400mg Fe3O4@C1-SO3H and 400mg of the above-treated cotton / paper and add them to a 15mL pressure-resistant tube. Then add 10mL of deionized water and a high-temperature resistant magnetic dome. Finally, tighten the cap and fix it inside the coil of the high-frequency electromagnetic induction device, ensuring that the magnetic dome at the bottom is below the coil (to keep the magnetic dome away from the magnetic field and prevent it from being heated).

[0337] Reaction conditions: Rotation speed 1000 rpm, reaction time 9 h, magnetic field strength 0.5 T, magnetic field frequency 380 kHz, continuous operation. After the reaction, the total reducing sugar yield of the reaction solution was determined by the 3,5-dinitrosalicylic acid method. A standard curve for total reducing sugar was constructed (using cellobiose as the standard solution). The products were detected by HPLC (high performance liquid chromatography), and the yield was calculated using the standard curve method (using glucose as the standard solution).

[0338] The detection conditions were as follows: Total reducing sugar determination equipment: UV-Vis spectrophotometer; cuvettes: quartz cuvettes; detection wavelength: 540 nm; chromatographic column: SUGAR-SH1011; column temperature: 30℃; detector: differential refractive index detector (2414 RI Detector); mobile phase: 5 mmol / L sulfuric acid; flow rate: 0.6 mL / min.

[0339] In comparison, the operation process is similar to that of Example 31 above, except that the frequency of the magnetic field is changed to 440 kHz and 500 kHz. The reaction results are shown in Table 25 below:

[0340] Table 25

[0341]

[0342] As can be seen from the above embodiments, this invention introduces various methods for preparing magnetic solid acids for polysaccharide hydrolysis and the application of electromagnetic induction heating technology, enabling efficient and directional hydrolysis of polysaccharides through electromagnetic induction heating. This invention has the following advantages: it uses inexpensive raw materials, offers high selectivity, utilizes high-acidity catalysts, is simple to operate, operates under mild reaction conditions, and achieves higher yields than traditional heating methods. Due to its magnetic properties, the reacted solid material can be easily separated from the catalyst using a magnet for secondary utilization, reducing energy consumption. Compared to traditional external heating, this invention's high-frequency electromagnetic induction heating method offers higher selectivity and yield for polysaccharide hydrolysis, demonstrating strong industrial application prospects and promotional value.

Claims

1. The application of magnetic solid acid in the high-frequency electromagnetic heating hydrolysis of polysaccharides to prepare glucose, characterized in that: Glucose was prepared by hydrolyzing polysaccharides using magnetic solid acid as a catalyst and high-frequency electromagnetic heating. The magnetic solid acid has a core-shell structure, with a magnetic material as the core and an outer shell material whose surface is modified with acidic groups and adsorption groups. The magnetic solid acid is prepared by the following method: By encapsulating different magnetic cores within shells of different properties, magnetic solid acid precursors with core-shell structures are obtained. Then, by sequentially modifying the surface with adsorption groups and sulfonic acid groups, magnetic solid acids can be obtained. The magnetic core is a magnetic material, specifically one of Fe3O4, Co, Ni, or FeCo magnetic nanoparticles. The outer shell is one of carbon shell, SiO2 shell, and nitrogen-containing carbon shell; The adsorption group refers to a weakly acidic group that binds to a glycosidic bond, including one or more of -Cl, -OH, and -COOH.

2. The application according to claim 1, characterized in that: The polysaccharide refers to a sugar whose structural unit is glucose and is formed by glycosidic bonds, including one or more of starch and cellulose.

3. The application according to claim 1, characterized in that: Before the hydrolysis reaction, the reaction substrate polysaccharide is pretreated, and the pretreatment methods include mechanical ball milling and ionic liquid treatment.

4. The application according to claim 1, characterized in that: The magnetic field range during high-frequency electromagnetic heating is 380-500 KHz.

Citation Information

Patent Citations

  • Method and apparatus for treatment of biomass substrates

    CN104603154A

  • Preparation of magnetic nano solid acid and application of magnetic nano solid acid in lignocellulose hydrolysis

    CN111729674A